Power consumption pattern modeling for effective distribution network planning - Chai, Choung Jung (Universiti Malaysia Sarawak, (UNIMAS), 2009)
The demand for electricity is increasing due to population growth. The power consumption pattern become critical issues to be investigated so that the network can be planned, designed and operated efficiently to meet the increasing yearly demand. In this study, multistage cluster sampling is used to calculate the sample size. Power consumption data for every 15 minutes time interval was recorded by using EDMI Mk.6 Genius polyphase electronic (E3) meter. Once power consumption data is collected, power consumption pattern, load factor, diversity factor, after diversity maximum demand, distribution transfonner size and l1kV cable size can be detennined. Analysis on temperature sensitivity related to the demand and method to improve overall load factor will be carried out. The result shows that power consumption pattern is influenced by consumer behaviour, time and weather. For the consumer behaviour factor, differences in numbers, sizes and types of electrical appliance will greatly influence the demand and maximum demand of the power consumption pattern. For time factor, demand for domestic 'consumer is high during nighttime as compared to daytime. Weather is also a factor which can affect the demand. In this study, analysis on temperature sensitivity related to the demand shows that when the temperature increases, the demand will also increase. The result shows that commercial unit floor has the highest value of after diversity maximum demand followed by detached house, semi-detached house, terrace house and residential unit floor. Based on the value of after diversity maximum demand and the unit of different types of consumers needed, more accurate total electrical load, distribution transformer size and 11 kV cable size can be determined. The power consumption pattern model had been created by using graphical user interface. By entering the unit of different types of consumers needed, this model is able to determine accurately total electrical load, distribution transformer size and the 11 kV cable size needed.